TINJAUAN EFEKTIVITAS METODE HANLON DALAM MENENTUKAN PRIORITAS MASALAH PENGELOLAAN OBAT DI RUMAH SAKIT : NARRATIVE REVIEW: Review of the Effectiveness Hanlon Method in Determining Drug Management Problem Priorities in Hospitals: Narrative Review - Isnaini Adinda Pratiwi; Diesty Anita Nugraheni (JFL : Jurnal Farmasi Lampung, 2026)
Drug management is an important aspect and a focus in the Pharmacy due to its relation to the drug supply in hospitals. Having a good drug management system is an effort to enhance health services in the community, particularly in pharmaceutical services. However, in practice, managing medications is not an easy task and many issues arise. Pharmaceutical services are divided into two categories: clinical pharmacy services and management of pharmaceutical preparations. The management of preparations begins with selection, planning, procurement, storage, distribution, control, recording and reporting, as well as destruction, which is carried out in pharmaceutical facilities such as pharmacies, community health centers, clinics, and hospitals. This research aims to review the effectiveness of the Hanlon method in determining priorities for medication management issues in hospitals. The research method employed involves reviewing several sources including journals and articles into a narrative review format. The results of this study indicate that the Hanlon method is effective to prioritize medication management issues found in hospitals. Keywords: Hanlon Method, Priority Issues, Drug Management, Hospital